Assessment of radiation dose in nuclear cardiovascular imaging using realistic computational models. Issue 6 (21st May 2015) - Xie, Tianwu; Lee, Choonsik; Bolch, Wesley E.; Zaidi, Habib
Abstract : Purpose: Nuclear cardiology plays an important role in clinical assessment and has enormous impact on the management of a variety of cardiovascular diseases. Pediatric patients at different age groups are exposed to a spectrum of radiation dose levels and associated cancer risks different from those of adults in diagnostic nuclear medicine procedures. Therefore, comprehensive radiation dosimetry evaluations for commonly used myocardial perfusion imaging (MPI) and viability radiotracers in target population (children and adults) at different age groups are highly desired. Methods: Using Monte Carlo calculations and biological effects of ionizing radiation VII model, we calculate the S ‐values for a number of radionuclides (Tl‐201, Tc‐99m, I‐123, C‐11, N‐13, O‐15, F‐18, and Rb‐82) and estimate the absorbed dose and effective dose for 12 MPI radiotracers in computational models including the newborn, 1‐, 5‐, 10‐, 15‐yr‐old, and adult male and female computational phantoms. Results: For most organs, 201 Tl produces the highest absorbed dose whereas 82 Rb and 15 O‐water produce the lowest absorbed dose. For the newborn baby and adult patient, the effective dose of 82 Rb is 48% and 77% lower than that of 99m Tc‐tetrofosmin (rest), respectively. Conclusions: 82 Rb results in lower effective dose in adults compared to 99m Tc‐labeled tracers. However, this advantage is less apparent in children. The produced dosimetric databases for various radiotracers used in cardiovascular imaging, using new generation of computational models, can be used for risk‐benefit assessment of a spectrum of patient population in clinical nuclear cardiology practice.